Modified interaction: teaching-like and conversation-like discourse on grammar in ELF classrooms - Da Dilva Gomez, Ana; De Fina, Ana; Díaz de León, José María (Lenguas Modernas, 2017)
The main object of this study was to conduct an exploratory investigation on the ways in which teachers and learners interact when talking abrout grammar in EFL classes. The study was qualitative and process oriented. The subjects were one bilinguat EFL female teacher and an intermediate level group of 20 male and female young adult university estudents. Transcriptions were analysed first to identify the topics interaction. Secondly, the fragments centered around the topic of explicit grammar were selected for further analysis. Two main discourse types emerged which were classified as teaching-like and, conversalion-like discourse. The interactions identilied as conversationlike shared similarities with NS/NNS exchanges in a natural environment although they were centered on such a formal topic-like grammar. The appearance of conversation-like discourse was found to correlate with a specific type of two-way information-gap task identified as teacher and studeuts thinking-aloud about grammar.